State-business partnership in poverty reduction : a case study of three public-private partnerships in Swaziland - Mutsigwa, Joseph Kudzanai (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2009.